2015
DOI: 10.17795/zjrms-2179
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal Effect of Magnesium Oxide, Zinc Oxide, Silicon Oxide and Copper Oxide Nanoparticles Against Candida albicans

Abstract: AbsrtactBackground: Candidiasis is the most common fungal infection in human and warm-blooded animals. Candida albicans, is an opportunistic pathogen in immune suppressed hosts, like HIV infected and under chemotherapy patients. Since, antifungal drugs are limited and challenged by resistance. Thus discovering agents with antifungal properties and minimum side effects and toxicity is essential. Nano-agents such as metal oxide nano-particles have unique properties such as high surface to volume ratio that intro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
36
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(42 citation statements)
references
References 21 publications
(25 reference statements)
4
36
1
1
Order By: Relevance
“…On the other hand, Karimiyan, Najafzadeh, Ghorbanpour, and Hekmati-Moghaddam (2015) detected no antifungal effect of MgO NPs on the tested Candida albicans and the MIC was more than 3200 μg/ ml.…”
Section: Enzymatic Activitymentioning
confidence: 81%
See 1 more Smart Citation
“…On the other hand, Karimiyan, Najafzadeh, Ghorbanpour, and Hekmati-Moghaddam (2015) detected no antifungal effect of MgO NPs on the tested Candida albicans and the MIC was more than 3200 μg/ ml.…”
Section: Enzymatic Activitymentioning
confidence: 81%
“…These findings are consistent with our results, where the use of a dose as high as 8 mg/ml MgO NPs resulted in three‐log 10 reductions on the viable cell counts after 24 hr that increased progressively to reach 8.7‐log 10 reduction after 48 hr postincubation. On the other hand, Karimiyan, Najafzadeh, Ghorbanpour, and Hekmati‐Moghaddam () detected no antifungal effect of MgO NPs on the tested Candida albicans and the MIC was more than 3200 μg/ml.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of opportunistic fungal infections, particularly candidiasis, is increasing in immunocompromised patients, due to taking long-term antifungal agents, hospitalization, organ transplantation, and malignancies (1,2). Candida albicans are considered as an important opportunistic pathogen with the unique characteristic of transition of yeast form to hyphae (3), which leads to serious life-threatening infection in cases with immunodeficiency disorders (4,5).…”
Section: Introductionmentioning
confidence: 99%
“…A variety of synthetized nanoparticles with antifungal properties are under evaluation. It has been established that zinc oxide nanoparticles (ZnO NPSs) have appropriate antifungal traits; however, ZnO may increase the effectiveness of antifungal agents (1)(2)(3)(8)(9)(10). Moreover, in a recent study reported by Barad et al, zinc oxide nanoparticles coated by chitosan and chitosan-linoleic acid showed enhanced antifungal properties (1).…”
Section: Introductionmentioning
confidence: 99%
“…ZnO NPs showed killing ability versus a vast group of gram negative and positive bacteria 11 and fungi and particularly C. albicans. 12 Moreover exploring the mechanical effect of composite resin modified by ZnO NPs determined increasing compressive and shear without altering the flexural strength of composite resin, 13 from the other hand toxicity of Ag NPs to human cell and brown dicoloration of PMMA result in suspecting the use of this material any more. [14][15][16] Overall, Lower toxicity of ZnO NPs, their killing ability of C. albicans, white appearance and ability to reinforce of composite resin is some advantages of this material.…”
Section: Introductionmentioning
confidence: 99%